Geochemistry of the Cambrian Sirius Passet Lagerstätte, Northern Greenland. (2nd April 2014) - Boudec, Ange Le; Ineson, Jon; Rosing, Minik; Døssing, Lasse; Martineau, François; Lécuyer, Christophe; Albarède, Francis
Abstract The lower Cambrian Sirius Passet Lagerstätte (∼518 Ma) consists of mudstones about 8 m thick located in the Franklinian Basin of North Greenland. We analyzed major and trace elements plus the S, C, Cu, Fe, Zn, and Mo isotope compositions. Factor analysis allowed the lithology of the mudstone to be broken down into variable proportions of two inputs, a dry felsic component and a hydrous mafic component (smectite or chlorite). Zircons U‐Pb ages indicate multiple sources, the local Proterozoic basement of Northern Greenland (1250–2400 Ma) and Pan‐African felsic magmas (620–650 Ma) from across the Iapetus ocean. Diagenesis involved the reduction of Fe, S, and Mo from seawater and pyritization. The Sirius Passet Lagerstätte formed in oxygen‐starved muds inhibiting degradation of organic matter underneath a well‐ventilated water column. The chemistry of the samples, their very fine grain size, their apparent lack of graded bedding, and the age of zircons suggest that the Lagerstätte may represent wind‐blown dust deposited on the continental slope.